Workload of technical secondary school teachers: management and administration's perceptions - Shafie, Sharifah; Abdul Kadir, Suhaida; Asimiran, Soaib (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2014)
The Malaysian education system constantly undergoes changes. These changes have created an impact on teachers? workload. A study was conducted to identify the workload of technical secondary school teachers focusing on the management and administration of those teaching Integrated Living Skills (KHB). The respondents consisted of 284 KHB teachers in the state of Kedah. The contents of the questionnaire encompassed the amount of time allocated to perform tasks related to administration and management. The findings indicated that the average teacher workload in KHB management and administration is 8.76 hours per week. The implication of this study is that KHB teacher?s workload in management and administration should be reduced to ensure that they can focus on innovation in teaching and learning. It is proposed to create the post of workshop assistants similar to the laboratory assistants who assist the Science teacher.